DESIGN OF TEMPERATURE AND AIR HUMIDITY MONITORING INFORMATION SYSTEM BASED ON ANDROID AND IOT (INTERNET OF THINGS) - Alexander Victor Bukit; I Nengah Putra A; Febryan Galih Rahardi; Ahmadi Ahmadi (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
For a soldier, physical abilities are needed in every task implementation, so the daytime running activities become a compulsory menu for every soldier who is carrying out education. Both the basic military education and further education. According to health experts, benefit of jogging is to lose weight so as to avoid obesity, improve the ability of the lungs, heart and various other health benefits. However, we also have to pay attention to the temperature of the air because it is at a certain temperature, it will be very risky if we carry out the afternoon run. Not a few victims affected by heat stroke due to run during the day with high air temperatures. The current mechanism, temperature measurements are carried out manually by members of the local Satkes, then the Satkes report the results of temperature measurements to Binjas and then Binjas decide whether or not to run afternoons that day. After the decision was made, the Binjas reported to the guard division and the guard to spread the news through the prayer watch. Therefore, with this android-based temperature and humidity monitoring information system, we can easily find out whether today's temperature is safe or not to carry out daytime running activities.Keywords : Afternoon Run, Heat stroke, Android.